Renewable energy technologies, storage systems, and energy transition challenges: a comprehensive review - Rima Kerroumi (Institute of Advanced Engineering and Science, 2026)
This work focuses on the theoretical aspect, as the widespread use of renewable energy in all sectors contributes to enhancing energy security by reducing countries’ dependence on imported fossil fuels. Renewable energy sources are often more diverse, thus reducing the risk of supply disruptions. Therefore, renewable energies (REs), such as solar, wind, and hydroelectric power, can be produced domestically. However, the fundamental challenge lies in how to encourage and incentivize countries to transition to clean energy, as this transition faces several political and economic obstacles, infrastructure problems in most countries, instability, storage issues, initial costs, the need for large areas, and a lack of expertise and technical support, all of which hinder countries from moving forward toward a secure and clean future. Therefore, this study provides an analysis of various types of renewable energy, their operating principles, and their requirements, aiming to clarify and encourage the selection of energy sources based on each country’s financial and geographical capabilities. The study concludes with several findings, including that leading countries in this field have achieved profits, self-sufficiency, expanded their investments, and created numerous jobs – a strategic approach to protecting themselves from the volatility of fossil fuel prices in global markets. Advances in what we call new energies offer a glimpse of a more stable, sustainable, and livable future. This transformation is also essential for economic, environmental, and geopolitical reasons if we are to preserve our planet.